Combining fundamental and technical analyses for better stock selection: An empirical study on Bursa Malaysia - Lim, Mei Ching; Nor, Normaziah Mohd; Selamat, Aslam Izah; Ibrahim, Siti Nur Iqmal (The Economics and Finance Letters, 2025)
This research aims to examine the impact of fundamental and technical analyses in stock selection, focusing on the FBM 100 index stocks in Bursa Malaysia from 2021 to 2023. The design of this research is based on the filtration of variables within fundamental and technical analyses and the application of Monte Carlo simulations using Python. Using a filtration approach, the Monte Carlo simulations are applied to varying combinations of fundamental metrics, namely price-earnings ratio, dividend yield, price-to-book ratio, and earnings per share, as well as technical indicators such as moving average convergence divergence (MACD), moving average crossovers, and relative share price momentum. The strategy that employs all the fundamental and technical analysis filters achieved a monthly return of 3.34% and a weekly return of 1.05%, compared to just 0.60% and 0.23% without filters. Although the higher returns are accompanied by higher volatility, the hybrid combination of both fundamental and technical analyses yields better risk-adjusted performance. Within the scope of fundamental analysis, this study further reveals that sector affiliation is a significant determinant of share price performance. This study highlights the complementary nature of fundamental and technical analyses, which offer a practical, flexible, and hybrid stock selection framework for enhancing equity investment outcomes.